Postpartum depression among women with unintended pregnancy - Cynthia Nunes de Oliveira Brito; Sandra Valongueiro Alves; Ana Bernarda Ludermir; Thália Velho Barreto de Araújo (Universidade de São Paulo, 2015)
OBJECTIVE To analyze the association between unintended pregnancy and postpartum depression. METHODS This is a prospective cohort study conducted with 1,121 pregnant aged 18 to 49 years, who attended the prenatal program devised by the Brazilian Family Health Strategy, Recife, PE, Northeastern Brazil, between July 2005 and December 2006. We interviewed 1,121 women during pregnancy and 1,057 after childbirth. Unintended pregnancy was evaluated during the first interview and postpartum depression symptoms were assessed using the Edinburgh Postnatal Depression Screening Scale. The crude and adjusted odds ratios for the studied association were estimated using logistic regression analysis. RESULTS The frequency for unintended pregnancy was 60.2%; 25.9% presented postpartum depression symptoms. Those who had unintended pregnancies had a higher likelihood of presenting this symptoms, even after adjusting for confounding variables (OR = 1.48; 95%CI 1.09;2.01). When the Self Reporting Questionnaire (SRQ-20) variable was included, the association decreased, however, remained statistically significant (OR = 1.42; 95%CI 1.03;1.97). CONCLUSIONS Unintended pregnancy showed association with subsequent postpartum depressive symptoms. This suggests that high values in Edinburgh Postnatal Depression Screening Scale may result from unintended pregnancy.